EVM.net : an extensive tool for web content management - Fontoura, Marcelo (2005)
By the late 90’s Brazil experienced the “boom” of Internet although its use was restricted to the universities and large companies. On this context the Parliament of the state of Rio Grande do Sul (Southern Brazil) has sponsored the development of a tool for publishing its contents. That tool should have some characteristics like be portable, “plug-and-play”. Responding to the demand has emerged EVM.net (acronym for modular virtual structure on the Internet), a GPL integrated solution for publishing and managing web contents. EVM.net follows a distributed information architecture, each user is responsible for maintaining his contents. The system has been conceived to be scaleable: its architecture has been planned following the metaphor of a building. The foundations contain the security tools and the persistence model, while the other stages are customized for each demand. EVM.net also contains algorithms for query optimization and phonetic search for Brazilian Portuguese Recently the tool had been used to implement the Extensive Communication Model, which is based on interactivity, hypertextuality, and hypermediation. Currently, EVM.net is being used at many institutions like the University of Brasilia, the Federal Senate of Brazil and the Brasilia’s Federation of Industries.